Pendampingan Belajar Bahasa Inggris (Basic English) pada Anak Usia Sekolah Dasar - Azahra, Silva (Pucuk Rebung: Jurnal Pengabdian kepada Masyarakat, 2023)
Assistance in learning English for elementary school-age children is important in developing their language skills. This mentoring program is designed to introduce children to English in a fun and effective way. This includes the use of a variety of learning methods appropriate to the child's developmental level. This English learning assistance for elementary school-age children aims to create a positive and enjoyable learning environment, stimulate children's interest in English, and help them develop communication skills that will be useful throughout their lives. The method used is learning to sing along. This learning assistance is carried out three times a week, starting from 19.00 WIB until finished. Based on the results of evaluations and observations, there was an increase in students' learning motivation and students' understanding of English.